N-Acylthioamide Metal Complexes-1: N-Benzoylthiobenzamide Complexes Of Manganese (II), Iron (II), Cobalt (II), Nickel (II). Copper (II) and Zinc (II), Sulphates (Journal of Science and Technology, 2016)
Metal (II) complexes of the type [M(N-BTB3) ]SO, where N-BTB = C6 H5CO.NFICSC6H5, M =Mo(II), Fe(TD, Co(II), Ni(II) and Znal); and also [Cu(N-BTB)2]SO4, have been synthesized by solid - solid interaction and characterized by means of a number of techniques including elemental analysis, IR spectra, magnetic susceptibility measurements and electronic (reflectance) spectra. All the complexes exhibit octahedral stereochemistry except the Cu (II) complex which is square planar. IR data indicates that the N-Bermoylthiobenzamide coordinates to the metal ions in its trans-trans configurational form.